A house between homes : youth in the foster care system - Libal, Joyce (Broomall, Pa. : Mason Crest Publishers, 2004)
Discusses the laws that govern the foster care system, the newest and most innovative programs available today and provides an overview of the history of foster care, including the orphan trains and the British home children.
Cradled by uncertainty -- Coloring outside the lines -- The discovery -- Emergency shelter -- What's next? -- The waiting game -- A new home -- Stepping into tomorrow.
Includes bibliographical references (p. 121-122) and index.
Keywords: Foster home care -- United States -- Juvenile literature; Children -- Legal status, laws, etc. -- United States -- Juvenile literature; Abused children -- Psychology -- Juvenile literature; Foster home care; Foster home care -- Juvenile literature; Children -- Legal status, laws, etc. -- Juvenile literature; Child abuse -- Psychological aspects -- Juvenile literature